2022
DOI: 10.1192/bjo.2022.543
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of family psychoeducation for major depressive disorder: systematic review and meta-analysis

Abstract: Background Although its effect has not been verified, family therapy – such as family psychoeducation (FPE) – is a widely used intervention for treating major depressive disorder (MDD). To our knowledge, no systematic review and meta-analysis exists that examines the effect of FPE on MDD. Aims To assess evidence on the effectiveness of FPE on depressive symptoms in people with MDD. Method We searched several databases – including PubMed, MEDLINE and Web of Science, amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 66 publications
0
11
0
1
Order By: Relevance
“…It has been shown that multicomponent strategies applied in patients improve symptoms of depression ( 45 ). In this respect, it seems that components of demonstrated effectiveness, such as psychoeducation ( 46 ) and behavioral activation based intervention ( 47 , 48 ) can contribute to the reduction of depressive symptoms. This identifies the need to improve the training and strengthening of patients in self-motivation, self-control and monitoring of their disease.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that multicomponent strategies applied in patients improve symptoms of depression ( 45 ). In this respect, it seems that components of demonstrated effectiveness, such as psychoeducation ( 46 ) and behavioral activation based intervention ( 47 , 48 ) can contribute to the reduction of depressive symptoms. This identifies the need to improve the training and strengthening of patients in self-motivation, self-control and monitoring of their disease.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of external validity, our study took place in a specific geographical, clinical and cultural context, and focused only on family involvement for persons with psychotic disorders. However, there is increasing evidence that these interventions are relevant to other patient groups ( 53 , 54 ), as well as in other sociocultural contexts ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in patients with major depression have found positive outcomes of family interventions in alleviating depressive symptoms. 48 This suggests that clinical workers should conduct family-based psychosocial interventions to prevent and treat PSD. (3) Family members should improve family functioning, including improving problem-solving skills, providing good care, offering adequate emotional support and communicating effectively to decrease stroke patients’ depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%